2012
DOI: 10.1177/039463201202500304
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Yes-Associated Protein in Gastric Adenocarcinoma and Inhibitory Effects of its Knockdown on Gastric Cancer Cell Proliferation and Metastasis

Abstract: Yes-associated protein (YAP) has been implicated as an oncogene in multiple human cancers. In the present study, human gastric adenocarcinoma tissues of different grades (N=78) were collected and the mRNA and protein expression of YAP and phosphorylated YAP (p-YAP) in gastric adenocarcinomas were evaluated using immunohistochemistry, Real-time PCR and Western blot assays. Then, human gastric cancer SGC-7901 cells were stably transfected with lentivirus-mediated YAP small hairpin RNA (shRNA). The expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 24 publications
4
31
0
Order By: Relevance
“…As a newly discovered cell signal transduction pathway, the Hippo signaling pathway has important roles in regulating the volume and size of organs (3,4). YAP upregulation has been identified in various cancer types, including ovarian, lung, liver, gastric and prostate cancer and it has been associated with tumor progression and sensitivity to chemotherapy, indicating that YAP participates in tumor development (5)(6)(7)(8)(9). YAP has been reported to contribute to the resistance of various cancer types to chemotherapy drugs (10).…”
Section: Introductionmentioning
confidence: 99%
“…As a newly discovered cell signal transduction pathway, the Hippo signaling pathway has important roles in regulating the volume and size of organs (3,4). YAP upregulation has been identified in various cancer types, including ovarian, lung, liver, gastric and prostate cancer and it has been associated with tumor progression and sensitivity to chemotherapy, indicating that YAP participates in tumor development (5)(6)(7)(8)(9). YAP has been reported to contribute to the resistance of various cancer types to chemotherapy drugs (10).…”
Section: Introductionmentioning
confidence: 99%
“…They are expressed on the tumour cell surface, activate pro-MMP to exacerbate the malignancy, and are considered a powerful indicator of distant metastasis of cancer [38]. Our previous study has shown that LATS1/YAP signalling involves in tumour growth and invasion through regulation of the expression of Ki-67 and MMP-2 [39]. Furthermore, our present finding showed that, 17-AAG inhibited LAC cell growth and invasion with the decreased expression of Ki-67 and MMP-2, suggesting that LATS1/YAP signalling might mediate 17-AAG suppression of tumour growth and invasion via regulation of Ki-67 and MMP-2 expression in LAC cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, a growing body of evidence indicates that YAP and TAZ also play a role in gastric cancer. YAP expression is commonly observed in GC samples and GC cell lines, and its expression and nuclear localization correlate with poor prognosis (Kang et al, 2011;Song et al, 2012;Zhang et al, 2012). Relevantly, YAP expression in the GC cell line MKN-28 modulates actin remodeling and promotes cell migration, while the loss of YAP induces cell stiffening and impaired migration (Qiao et al, 2017).…”
Section: Future Directions and Conclusionmentioning
confidence: 99%